ANALISIS PENINGKATAN KETERAMPILAN MENULIS SASTRA ANAK SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN KREATIF (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing skills in children’s literature at the elementary school level still face various challenges, particularly in idea development, text structure, and expressive ability. This study aims to examine the improvement of children’s literary writing skills through a creative learning approach in elementary schools. The method used is a literature review by analyzing various relevant scientific sources, which are then thematically analyzed to obtain a comprehensive understanding of creative learning strategies and students’ writing outcomes. The findings indicate that creative learning strategies that are thematic, varied, systematic, and technology- and collaboration-based are able to improve students’ writing quality in terms of narrative structure, diction selection, and idea development. In addition, creative learning strategies also encourage active student engagement in the writing process, resulting in more structured and meaningful simple literary works. Therefore, creative learning is recommended as an effective approach to continuously improve children’s literary writing skills in elementary schools.